Lutidinium-based ionic liquids for efficient dissolution of cellulose. (16th January 2019) - Samikannu, Rakesh; Shukla, Shashi Kant; Samikannu, Ajaikumar; Mikkola, Jyri-Pekka
Abstract : Herein, we have studied the potential of lutidinium-based ionic liquids in the dissolution of cellulose as confirmed by the X-ray diffraction (XRD), scanning electron microscopy (SEM) and 13 C CP/MAS NMR, spectroscopic methods. Abstract : Herein, we have studied the potential of lutidinium-based ILs (1-allyl-3, 5-dimethylpyridinium chloride [3, 5-ADMPy]Cl and 1-allyl-3, 4-dimethylpyridinium chloride [3, 4-ADMPy]Cl) in the dissolution of cellulose, and their structures were confirmed by 1 H and 13 C NMR spectra, respectively. [3, 5-ADMPy]Cl exhibited the highest capacity in cellulose dissolution. In fact, it dissolved 20 wt% of cellulose within 12 min and 26 wt% of cellulose in 35 min at 118 °C. The crystallinity and morphology of native and regenerated cellulose were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM) and CP/MAS 13 C NMR spectroscopy. These techniques clearly suggest that the crystallinity of cellulose is reduced upon treatment in lutidinium-based ILs. The thermogravimetric analysis (TGA) showed that regenerated cellulose had thermal stability close to that of native cellulose.